Association of hypokalaemia and hypophosphataemia. Issue 5680 (15th November 1969) - Anderson, D. C.; Peters, T. J.; Stewart, W. K.
Abstract : A prospective study of 13 patients with hypokalaemia due to a variety of causes demonstrated that six had hypophosphataemia. In 10 patients the plasma inorganic phosphate level rose on correction of the hypokalaemia. Before treatment seven patients had an excessive rate of excretion of phosphate relative to creatinine in the urine. Following correction of the hypokalaemia 11 patients had an increase in renal tubular reabsorption of phosphate relative to creatinine. It is suggested that hypokalaemia may be causally related to the hypophosphataemia, and that in chronic potassium depletion this may affect bone mineralization.